Problematika Guru dalam Mengintegrasikan Nilai-Nilai Lokal Tengger ke dalam Pembelajaran SD/SMP di Kabupaten Probolinggo - Rosyidah, Tika Himmatur; Shinvani, Rosa Diah (Nexus Publishing, 2024)
The purpose of this research is to identify, describe or depict the problems and needs of teachers in Probolinggo Regency in integrating local Tengger values into learning. A qualitative approach is used to match the descriptive method employed. The results of the questionnaire survey conducted through Google Forms reveal obstacles faced by teachers in Probolinggo Regency. The results show the problems of local wisdom with modernization. The context of local values such as 'pakne' if implemented in learning, because not all connotations of the meaning of local Tengger values will have a positive impact on learning,